(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to examine the influence of content marketing and product reviews on TikTok Shop toward purchasing decisions of Skintific skincare products in Bima City. This research employed a quantitative approach with an associative design. The population consisted of TikTok users in Bima City who had been exposed to Skintific content, while 96 respondents were selected using purposive and accidental sampling techniques. Data were collected through a structured questionnaire using a five-point Likert scale. The research instrument measured three variables, namely content marketing, product reviews, and purchasing decisions. Data were analyzed using multiple linear regression with the assistance of SPSS after passing validity and reliability testing. The findings indicate that neither content marketing nor product reviews had a significant partial effect on purchasing decisions. Likewise, both variables simultaneously did not significantly influence purchasing decisions. These results suggest that consumers’ decisions to purchase Skintific skincare products are not primarily determined by marketing content or product reviews on TikTok Shop. The coefficient of determination showed that the contribution of both variables was relatively low, indicating that purchasing decisions are more strongly influenced by other factors, such as product quality, brand trust, price perception, promotional strategies, or consumer preferences. This study highlights the importance of considering broader determinants of consumer behavior in the digital marketplace